Aerobic and anaerobic fungal metabolism and Omics insights for increasing polycyclic aromatic hydrocarbons biodegradation. Issue 2 (March 2017) - Aydin, Sevcan; Karaçay, Hatice Aygün; Shahi, Aiyoub; Gökçe, Selen; Ince, Bahar; Ince, Orhan
Abstract: During the 19th century, increasing human activity followed by great use of fossil fuels and the production of manifold aromatics including polycyclic aromatic hydrocarbons (PAHs) induced the generation of aromatic end-products. PAH are toxic to human health since they have been classified as pollutants and may reduce the biodiversity of natural ecosystems. They may form extensive global contaminants which pose a threat to entire world. This study focuses on summarizes recent information of PAHs biodegradation by aerobic and anaerobic fungi. Such information develops a new point of view on how organic molecules including PAHs are metabolically degraded in a complicated ecosystem and assists the foundation of new decontamination strategies due to the microbial interactions between fungi and their associates. Emerging integrative approaches including metagenomics, metatranscriptomics, metabolomics, and metaproteomics are studied in order to understand how these approaches give insight into decipher the molecular mechanisms of degradation of PAHs by fungi at the single species and community levels.